2016
DOI: 10.1155/2016/6843121
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression in HCC Patient with Portal Vein Tumor Thrombosis after Intraportal Radiofrequency Thermal Ablation

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide. Portal vein tumor thrombosis (PVTT) is a frequent entity in HCC, which strictly limits the gold standard treatment options such as surgical resection and transarterial chemoembolization. Therefore, the prognosis of patients with PVTT is extremely poor and an emergence of seeking an alternative option for intervention is inevitable. We present a case of a 60-year-old male patient with HCC induced PVTT who was subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The criteria for PVTT classification was used as before 11,24,25,[28][29][30] and the types of PVTT were classified submit your manuscript | www.dovepress.com…”
Section: Classification Of Pvttmentioning
confidence: 99%
“…The criteria for PVTT classification was used as before 11,24,25,[28][29][30] and the types of PVTT were classified submit your manuscript | www.dovepress.com…”
Section: Classification Of Pvttmentioning
confidence: 99%
“…Thermal ablation of portal vein tumor thrombus is rarely considered given the portal vein's the tumor's oblong shape as well as its proximity to critical structures, like the hepatic artery and bile ducts. However, one recent report has shown good results after endoluminal ablation followed by stenting (81).…”
Section: Treatmentmentioning
confidence: 99%
“…This study's results showed that the EP-RFA procedure led to an improvement in liver function in around 70% of cases, accompanied by low AEs. Prior studies also reported the excellent safety of the procedure, with an increase in PV velocity after PVR-EPRFA-ST [10][11][12][13][14][15]23] (Table 3). PV stenting was reported to be safe with excellent technical success, resulting in the relief of portal obstruction with a post-procedure PV patency greater than 13 months, enabling patients to pursue additional treatments such as TACE, TARE, surgery, and chemotherapy.…”
Section: Discussionmentioning
confidence: 82%
“…It was adapted as a novel treatment option for HCC PVTT utilizing a percutaneously delivered endoluminal probe mated to a 480 kHz alternating-current generator, resulting in a frictional heat-based cylindrical coagulative necrosis of PVTT in a 2-3 mm radius surrounding the probe, resulting in PV recanalization [8]. EP-RFA aims to alleviate portal obstruction and enable patients to pursue additional treatments such as TACE, transarterial radioembolization (TARE), surgery, and chemotherapy [8][9][10][11][12][13][14][15]. The goal of this study was to investigate the feasibility, safety, and clinical outcomes of a combination of EP-RFA and PV stent placement in a cohort of patients with HCC and PVTT.…”
Section: Introductionmentioning
confidence: 99%